SNAP Participation and Diet-Sensitive Cardiometabolic Risk Factors in Adolescents - Leung, Cindy W. (Am J Prev Med, 2017)
INTRODUCTION: Previous research suggests participation in the Supplemental Nutrition Assistance Program (SNAP) is associated with poorer adult cardiometabolic health; the extent to which these associations extend to adolescents is unknown. Differences in diet quality, obesity, and cardiometabolic risk factors were examined among SNAP participants, income-eligible nonparticipants, and higher-income adolescents. METHODS: The study population comprised 4,450 adolescents ≤300% federal poverty level from the 2003–2010 National Health and Nutrition Examination Survey. Generalized linear models were used to examine associations between SNAP participation and the Alternate Healthy Eating Index-2010. Linear and logistic regression models were used to examine associations between SNAP participation, obesity, and risk factors comprising the metabolic syndrome. Data were analyzed in 2015. RESULTS: All surveyed adolescents consumed inadequate amounts of vegetables, fruits, whole grains, and long-chain fatty acids, while exceeding limits for sugary beverages, processed meats, and sodium. Although there were few dietary differences, SNAP participants had 5% lower Alternate Healthy Eating Index-2010 scores versus income-eligible nonparticipants (95% CI= −9%, −1%). SNAP participants also had higher BMI-for-age Z scores (β=0.21, 95% CI=0.01, 0.41), waist circumference Z scores (β=0.21, 95% CI=0.03, 0.39), and waist-to-height ratios (β=0.02, 95% CI=0.00, 0.03) than higher-income nonparticipants. SNAP participation was not associated with most cardiometabolic risk factors; however, SNAP participants did have higher overall cardiometabolic risk Z scores than higher-income nonparticipants (β=0.75, 95% CI=0.02, 1.49) and income-eligible nonparticipants (β=0.55, 95% CI=0.03, 1.08). CONCLUSIONS: Adolescent SNAP participants have higher levels of obesity, and some poorer markers of cardiometabolic health compared with their low-income and higher-income counterparts.